Could procalcitonin be used as an indicator to start or stop antibiotics for acute upper and lower respiratory infections?. Issue 12 (December 2015) - Lu, Stephen; Brennan, Michal
Abstract : Evidence‐Based Answer : Procalcitonin‐guided algorithms for the initiation and stopping of antibiotics in acute upper and lower respiratory infections (ARIs) decreased antibiotic usage and duration in the primary care setting and was not associated with higher mortality rates or treatment failures (SOR: A, meta‐analysis of RCTs).